Dose‐dependent inhibition of demyelination and microglia activation by IVIG. Issue 11 (23rd September 2016) - Winter, Meike; Baksmeier, Christine; Steckel, Julia; Barman, Sumanta; Malviya, Manish; Harrer‐Kuster, Melanie; Hartung, Hans‐Peter; Goebels, Norbert
Abstract: Objective: Intravenous immunoglobulin (IVIG) is an established treatment for numerous autoimmune conditions. Clinical trials of IVIG for multiple sclerosis, using diverse dose regimens, yielded controversial results. The aim of this study is to dissect IVIG effector mechanisms on demyelination in an ex vivo model of the central nervous system (CNS)‐immune interface. Methods: Using organotypic cerebellar slice cultures (OSC) from transgenic mice expressing green fluorescent protein (GFP) in oligodendrocytes/myelin, we induced extensive immune‐mediated demyelination and oligodendrocyte loss with an antibody specific for myelin oligodendrocyte glycoprotein (MOG) and complement. Protective IVIG effects were assessed by live imaging of GFP expression, confocal microscopy, immunohistochemistry, gene expression analysis and flow cytometry. Results: IVIG protected OSC from demyelination in a dose‐dependent manner, which was at least partly attributed to interference with complement‐mediated oligodendroglia damage, while binding of the anti‐MOG antibody was not prevented. Staining with anti‐CD68 antibodies and flow cytometry confirmed that IVIG prevented microglia activation and oligodendrocyte death, respectively. Equimolar IVIG‐derived Fab fragments or monoclonal IgG did not protect OSC, while Fc fragments derived from a polyclonal mixture of human IgG were at least as potent as intact IVIG. Interpretation: Both intact IVIG and Fc fragments exert a dose‐dependent protective effect on antibody‐mediated CNS demyelination and microglia activation by interfering with the complement cascade and, presumably, interacting with local immune cells. Although this experimental model lacks blood–brain barrier and peripheral immune components, our findings warrant further studies on optimal dose finding and alternative modes of application to enhance local IVIG concentrations at the site of tissue damage.